Attitude of Nutrition Experts Toward Psychotherapy and Virtual Reality as Part of Obesity Treatment—An Online Survey - Gemesi, Kathrin; Holzmann, Sophie Laura; Hochrein, Regine; Döllinger, Nina; Wienrich, Carolin; Weinberger, Natascha-Alexandra; Luck-Sikorski, Claudia; Holzapfel, Christina (Frontiers in Psychiatry, 2022)
Background: The management of obesity requires lifestyle-based interventions covering nutrition, physical activity, and behavior. As part of cognitive behavioral therapy (CBT), body image therapy approaches can be used not only by psychotherapists. One tool to conduct behavioral therapy is virtual reality (VR). It is unknown, whether nutrition experts conduct behavioral therapy, and whether they would like to use VR technology as a tool to conduct body image therapy as part of obesity management. Objective: This survey aimed to collect data from nutrition experts treating people with obesity about the status quo regarding behavioral and body image therapy as part of obesity management, and regarding their attitude toward VR in obesity therapy. Methods: The survey was conducted online in autumn 2020. Participants were recruited digitally through expert and professional associations. The standardized questionnaire included items concerning sociodemographic, professional status, behavioral therapy, body image, and VR. The descriptive analysis was performed with Excel, the subgroup analyses with R. Results: Data from 158 nutrition experts was analyzed. Participants were mostly female (98/102, 96.1 %) and had a mean age of 45.6 ± 11.3 years (n = 101). Most of the survey participants (93/124, 75 %) stated to use behavioral treatment methods in case of weight reduction as the primary target. More than half of the participants stated to address body image (99/150, 66.0 %). Almost all (111/112, 99.1 %) nutrition experts have never used VR-glasses. The suitability and importance of VR technology as part of obesity therapy was estimated as neutral by around 50 %. Overall, no statistically significant difference could be shown between age groups regarding attitudes towards VR in obesity treatment. Conclusion: The results of this non-representative survey indicate that nutrition experts do not use VR technology in nutrition counselling sessions to treat obesity. In addition, survey participants have a positive attitude to VR technology, whereas they are not familiar with this technology. In future, VR technology might support nutrition experts of every age using elements of body image therapy. Survey registration: the German Register of Clinical Studies (Registration number: DRKS00022853)